Diversitas dan kehilangan jenis ikan di danau-danau aliran Sungai Cisadane [Diversity and the fish species lost at the lakes of Cisadane river basin] - Renny Kurnia Hadiaty (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2011)
The study of diversity and the fish species lost was conducted at the lakes of the Cisadane river drainage in 2010. The aim of this study was to describe the recent fish diversity in the lakes of Cisadane river basin, then make the comparison with the number of species recorded based on the references data. The differences between the two data show the number of species lost. The result of the study showed a total of 32 species of 19 families and 5 order, those species were collected from 34 sites. Twenty four of the 32 species or 75% are native species; while the other 8 species or about 25% are introduce species. Total of the number of collected specimens about 1812 exs. There were 86 species live in the lakes of Cisadane river basin, since there is only 24 left, so the fish diversity lost in the lakes is about 72.1%. AbstrakPenelitian diversitas dan kehilangan spesies ikan di danau-danau dari daerah aliran Sungai Cisadane dilakukan pada tahun 2010. Penelitian ini bertujuan untuk mendapatkan gambaran keragaman jenis ikan di danau-danau pada daerah aliran Sungai Cisadane saat ini. Hasil ini kemudian dibandingkan dengan jumlah spesies ikan yang pernah hidup di wilayah perairan ini berdasarkan data pustaka. Selisih jumlah antara kedua data tersebut menunjukkan kehilangan spesies. Hasil penelitian di 34 stasiun mendapatkan 32 spesies ikan dari 19 famili dan lima ordo. Dua puluh empat jenis atau 75% diantaranya merupakan spesies asli, sedangkan delapan jenis atau 25% merupakan ikan introduksi. Studi pustaka menunjukkan ada 86 spesies ikan yang dulu hidup di danau-danau daerah aliran Sungai Cisadane, namun saat ini hanya dijumpai 24 spesies, dengan demikian laju kehilangan spesiesnya sekitar 72,1%.